Ser y vivir esclavo Identidad, aculturación y agency (mundos mediterráneos y atlánticos, siglos xiii-xviii) - P. Guillén, Fabienne; Salicrú i Lluch, Roser (Collection de la Casa de Velázquez, 2021)
Through a shifted and enriched approach, combining history and anthropology/sociology, this book addresses the forms of social integration and the multiple cultural hybridizations produced by slavery in the societies of Europe, Africa and America during the medieval and modern periods. Analyzing the normative contours used to define the identity of the slave, it then discusses his attempts and modalities of integration in the host societies, measuring the socialization process that may have resulted. Questioning the social mechanisms of the ancient societies that presided over the mixing of populations, as attested by the sources, is one of the areas that historians in this field (Atlantic societies, Maghreb) are most interested in. Among their main projects is that of deconstructing illusions of "racial" and cultural homogeneity in contemporary societies. A work on the acculturation and agency capacity of slaves, on the capacity of enslaved persons (not only freed) to exist as actors in the social sphere, particularly in the Iberian peninsula and the Mediterranean area, is the aim of this work. By proposing a history of Mediterranean brewing, it challenges preconceived ideas about cultural divisions and civilizational confinements.